Monitoring of Environmental Hg Occurrence in Tunisian Coastal Areas - Jebara, Amel; Lo Turco, Vincenzo; Faggio, Caterina; Licata, Patrizia; Nava, Vincenzo; Potortì, Angela Giorgia; Crupi, Rosalia; Mansour, Hedi Ben; Di Bella, Giuseppa (International journal of environmental research and public health, 2021)
Total mercury (Hg) was determined in 450 environmental samples (seawater, sediment plant and fish) from five Mahdia coastal areas (Tunisia). Tolerable Weekly Intake% (TWI) values, according to the European Food Safety Authority (EFSA), were calculated based on the average metal concentration in fish and the average weekly fish consumption rate. Hg was accumulated mainly in fish and in Posidonia oceanica leaves. Hg in sediment ranged from 1.88 μg/kg dry weight (d.w.) to 7.48 μg/kg d.w., while it was between 0.32 μg/kg and 0.19 μg/kg in seawaters. Our study showed high concentration in Posidonia oceanica in S3 (plant = 16.76 ± 4.48 μg/kg d.w.) as compared to those in S4 sites (plant = 5.33 ± 0.05 μg/kg d.w.). Concentrations for S. aurata and S. salpa in the Rejiche area exceeded the EC 1881/2006 legislation with values of 1.9 mg/kg and 2.5 mg/kg, respectively, and consumers may be exposed to high concentrations of Hg that exceeds the EFSA. The results showed that the fish species should be constantly monitored due to their TWI% of 154.5% for S. aurata and 209.8% S. salpa respectively.